EFL STUDENTS’ PERCEPTIONS AND CHALLENGES IN USING SELF-RECORDED VIDEO (SRV) FOR SPEAKING PRACTICE - Nur Hairunnisa' Annuri; Muhammad Mugni Assapari; Soni Ariawan; Malisa Malisa; Thanh Huy Nguyen (Universitas Islam Negeri Mataram, 2026)
Self-recorded video (SRV) has become a common digital task in EFL speaking classes, but its value needs to be understood beyond claims of direct speaking improvement. This study examines EFL students’ perceptions and challenges in using SRV as reflective speaking practice at the English Language Education Study Program of Universitas Islam Negeri Mataram. Using a descriptive mixed-methods design, data were collected from 70 third-semester students through a 16-item questionnaire and semi-structured interviews with six selected participants. Questionnaire responses were analysed descriptively, while interview data were interpreted thematically to explain students’ learning experiences. The findings show that SRV was perceived as useful because it gave students time to prepare, record, review, and revise their speaking performance. Students reported stronger self-awareness, especially in pronunciation, fluency, vocabulary use, and idea organisation, and many felt more confident because they could practise without the immediate pressure of live classroom performance. However, SRV also c reated challenges related to technical problems, editing skills, background noise, repeated recording, content organisation, camera anxiety, grammar monitoring, and script dependency. The study concludes that SRV is best used as a complementary reflective task supported by clear guidelines, feedback, and flexible implementation rather than as a substitute for classroom interaction.